Application of Science and Technology for Regional Development: Tangerine Agrotourism Selayar: Penerapan IPTEK Pengembangan Kewilayahan: Agrowisata Jeruk Keprok Selayar - Ilham Ahmad; Adilham Adilham; Karma Karma; Andryanto Aman (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Based on discussions with the local government, it was determined that the regional problem to be developed was ‘keprok’ citrus tourism in the village of Batangmata Sapo, Selayar Islands Regency. The partner's problem so far is that the ‘keprok’ citrus gardens owned have not been able to be used as a tourist attraction considering that Selayar ‘keprok’ citrus are located on an island that has very beautiful natural scenery. In general, the objectives of the first year Regional Development Science and Technology Program (PIPK) are (1) basic skills training for guides and agro-tourism entrepreneurship and the development and improvement of ago-tourism facilities (2) making a ‘keprok’ citrus-processed production house with the application of process technology and equipment for processing ‘keprok’ citrus, namely ‘keprok’ citrus juice and dodol oranges. The method used in this PPIK activity is the mentoring method carried out by students who have been trained in the MBKM program for activities in the application of process technology and equipment, training, mentoring and program evaluation. The results of the first year activities are: (1) the formation of a ‘keprok’ citrus picking tourist area which is carried out with the Forum Group Discussion (FGD) activity, (2) partners already have production houses and have skills in the production of processed ‘keprok’ citrus, namely orange juice and dodol oranges, (3) partners already have orange juice production equipment and orange dodol equipment through the instruction of process equipment from the two processed products. The conclusion of this activity is that the regional development of the Selayar ‘keprok’ citrus plantation sector has become a ‘keprok’ citrus agro-tourism area with the availability of facilities and infrastructure for the ‘keprok’ citrus picking agro-tourism area and a ‘keprok’ citrus production house that produces processed products of juice and ‘keprok’ citrus lunkhead. Abstrak Berdasarkan diskusi dengan pemerintah daerah maka ditetapkan permasalahan kewilayahaan yang akan dikembangkan adalah wisata jeruk keprok di desa Batangmata Sapo Kabupaten Kepulauan Selayar. Adapun permasalahan mitra selama ini adalah kebun jeruk keprok yang dimiliki belum mampu dimanfaatkan menjadi objek wisata mengingat jeruk keprok selayar berada dalam pulau yang memiliki pemandangan alam yang sangat indah. Secara umum tujuan program Penerapan Iptek Pengembangan Kewilayahan (PIPK) tahun pertama ini adalah (1) pelatihan keterampilan dasar pemandu dan kewirausahaan agrowisata dan pembangunan dan peningkatan fasilitas agowisata (2) membuat rumah produksi olahan jeruk keprok dengan penerapan teknologi proses dan peralatan olahan jeruk keprok yaitu jus jeruk keprok dan dodol jeruk. Metode yang digunakan pada kegiatan PIPK ini adalah model pendampingan ke mitra dengan metode training, mentoring ataupun coaching dengan metodologi dan materi-materi yang dilakukan oleh mahasiswa yang telah dilatih dalam program MBKM untuk kegiatan penerapan teknologi proses dan peralatan, pelatihan, pendampingan dan evaluasi program. Hasil dari kegiatan tahun pertama adalah: (1) terbentuknya kawasan wisata petik jeruk keprok yang dilakukan dengan kegiatan Forum Group Discussion (FGD), (2) mitra telah memiliki rumah produksi dan memilki keterampilan dalam produksi olahan jeruk keprok yaitu jus jeruk dan dodol jeruk, (3) mitra telah memiliki peralatan produksi jus jeruk dan peralatan dodol jeruk melalui intruduksi peralatan proses dari kedua produk olahan tersebut. Kesimpulan dari kegiatan ini adalah Pengembangan kewilayahan pada sektor perkebunan jeruk keprok Selayar telah menjadi sebuah kawasan agrowisata jeruk keprok dengan tesedianya sarana dan prasarana kawasan agrowisata petik jeruk keprok dan rumah produksi jeruk keprok yang memproduksi produk olahan jus dan dodol jeruk keprok.